076 Inflammatory complications of CGRP monoclonal antibodies. (23rd August 2021) - Ray, Jason C; Allen, Penelope; Bacsi, Ann; Bosco, Julian; Chen, Luke; Eller, Michael; Lim, Lyndell; Kua, Hock; Matharu, Manjit; Monif, Mastura; Stark, Richard; Hutton, Elspeth
Abstract : Background: CGRP monoclonal antibodies (mAb) are an effective new preventative treatment for episodic and chronic migraine, with a favourable adverse event profile. In addition to its role in mediating migraine attacks, CGRP is widely expressed throughout the body and in general has an anti-inflammatory/immunoregulatory role. Thus, inhibitory CGRP may potentiate a pro-inflammatory state. Methods/Results: We present a case series of eight patients with new or worsened inflammatory pathology in close temporal association with the start of CGRP mAb therapy. Conclusions: This case series provides novel insights on the potential molecular mechanisms and side-effect profile of CGRP inhibition and warrants vigilance in clinical practice.